Covid-19 and its impact to Indonesian higher educations – learning from IIU Malaysia - Zulhuda, Sonny (2020)
Discussing and assessing the implication of Covid-19 crisis to the Institutions of Higher Learnings and how IIUM has responded to it in its early phases